Deforestation and Welfare: Evidence from Africa - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2011)
This paper examines the effects of deforestation on the welfare of rural communities in the Congo Basin. Using moment conditions of agricultural and forest exploitations, findings indicate deforestation significantly improves welfare both at overall-rural and agricultural household per capita income levels. As a policy implication, in the process of forest exploitation a balanced approach is needed to take account of the interests of both rural communities, timber companies and international forest-sustainability standards. This should require among other things, the development and implementation of sustainable forest management plans by timber companies, exclusion from harvesting species that are important to local communities, compensation of timber companies for compliance with management plans as well as involvement of rural communities in monitoring the activities of timber companies.
Keywords: J10; L73; N50; O13; Q23; 330; Demography; Forestry; Agriculture; Welfare; Africa